Development and validation of nomograms to provide individualised predictions of seizure outcomes after epilepsy surgery: a retrospective analysis. Issue 3 (March 2015) - Jehi, Lara; Yardi, Ruta; Chagin, Kevin; Tassi, Laura; Russo, Giorgio Lo; Worrell, Gregory; Hu, Wei; Cendes, Fernando; Morita, Marcia; Bartolomei, Fabrice; Chauvel, Patrick; Najm, Imad; et al.
Summary: Background: Half of patients who have resective brain surgery for drug-resistant epilepsy have recurrent postoperative seizures. Although several single predictors of seizure outcome have been identified, no validated method incorporates a patient's complex clinical characteristics into an instrument to predict an individual's post-surgery seizure outcome. Methods: We developed nomograms to predict complete freedom from seizures and Engel score of 1 (eventual freedom from seizures allowing for some initial postoperative seizures, or seizures occurring only with physiological stress such as drug withdrawal) at 2 years and 5 years after surgery on the basis of sex, seizure frequency, secondary seizure generalisation, type of surgery, pathological cause, age at epilepsy onset, age at surgery, epilepsy duration at time of surgery, and surgical side. We designed the models from a development cohort of patients who had resective surgery at the Cleveland Clinic (Cleveland, OH, USA) between 1996 and 2011. We then tested the nomograms in an external validation cohort operated on over a similar period in four epilepsy surgery centres, in Brazil, France, Italy, and the USA. We assessed performance of the nomogram by calculating concordance statistics and assessing the calibration of predicted freedom from seizures with the reported freedom from seizures and Engel score of 1. Findings: The development cohort included 846 patients and the validation cohort included 604 patients. Variables included in the nomograms were sex, seizure frequency, secondary seizure generalisation, type of surgery, and pathological cause. In the development cohort, the baseline risk of complete freedom from seizures was 0·57 at 2 years and 0·40 at 5 years. The baseline risk of Engel score of 1 was 0·69 at 2 years and 0·62 at 5 years. In the validation cohort, the models had a concordance statistic of 0·60 for complete freedom from seizures and 0·61 for Engel score of 1. Calibration curves showed adequate calibration (judged by eye) of predicted and reported freedom from seizures, throughout the range of seizure outcomes. Interpretation: If validated in prospective cohorts, these nomograms could be used to predict seizure outcomes in patients who have been judged eligible for epilepsy surgery. Funding: Cleveland Clinic Epilepsy Center.